1989
DOI: 10.1007/bf00687715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic ethanol consumption beginning at adolescence: increased numbers of dendritic spines on cortical pyramidal cells in the adulthood

Abstract: To increase our understanding of the effects of chronic ethanol consumption beginning at adolescence, 25% ethanol in drinking water (v/v) was administered daily to young rats aged 45-50 days for 5 months. Increased numbers of dendritic spines on the apical dendrite of layer V pyramidal neurons of the somatosensory cortex (U-Mann-Whitney test, P less than 0.01-0.05) were found in almost every 50-micron-long segment over a distance of 500 microns from the cell body in ethanol-treated rats at the age of 195-200 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…These facts would thus argue that malnourishment is not a fac tor in the formation of hyperspiny neurons in this study. Ferrer [26] suggested that the increase in spines in alcohol-treated rats was due to a failure of the normal elimination of redundant synapses and that it may reflect delayed maturation of cortical circuits. In a Golgi study of reticular and nonreticular brainstem neurons from infants succumbing to sudden infant death syndrome (SIDS), Quattrochi et al [55] described hyper spiny dendrites in both cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…These facts would thus argue that malnourishment is not a fac tor in the formation of hyperspiny neurons in this study. Ferrer [26] suggested that the increase in spines in alcohol-treated rats was due to a failure of the normal elimination of redundant synapses and that it may reflect delayed maturation of cortical circuits. In a Golgi study of reticular and nonreticular brainstem neurons from infants succumbing to sudden infant death syndrome (SIDS), Quattrochi et al [55] described hyper spiny dendrites in both cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that enhancement of NGF-induced neurite outgrowth by ethanol was inhibited by downregulation of ,B, 6, and s isoforms of protein kinase C (PKC) (14). We also found that exposure to 25-100 mM ethanol for 2-6 days increased levels of mRNA (15) and protein (16) for 8 and s PKC and activated PKC in PC12 cells (16). Taken together, these findings suggest that ethanol enhances neurite formation by activating specific isozymes of PKC.…”
mentioning
confidence: 94%
“…Although early studies showed that ethanol inhibited neurite growth in some neurons (3,4), several reports (5)(6)(7)(8)(9)(10) indicate that ethanol markedly enhances neurite growth in several brain regions. For example, in adult rats, chronic ethanol exposure increases the length of dendrites in cerebellar Purkinje cells and hippocampal dentate granule cells and the number of dendritic spines on dentate granule cells and somatosensory cortical neurons (5)(6)(7)(8). Prenatal ethanol exposure increases dendritic arborization in layer Vb somatosensory corticospinal neurons and causes hyperdevelopment of hippocampal dentate granule cell axons (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results are representative of two independent experiments with similar results. dendritic segments in cerebellar Purkinje cells (Pentney and Quackenbush, 1990) and the number of dendritic spines on dentate granule cells (King et al, 1988) and somatosensory cortical pyramidal cells (Ferrer et al, 1989). In addition, ethanol has been shown to enhance neurite growth in cultured cerebellar neurons (Zou et al, 1993) and in growth factor-treated PC12 cells (Messing et al, 1991).…”
Section: Figmentioning
confidence: 98%